The Legal Certainty Versus National Economic Recovery: Peace Fines by Prosecutors in Corruption Crimes Comparative Law Perspective - Fradhana Putra Disantara; Mac Thi Hoai Thuong (PATTIMURA Legal Journal, 2025)
Introduction: The application of peace fines in corruption crimes in Indonesia creates a complex legal dilemma. The Prosecutor's Law grants prosecutors the authority to use peace fines in economic crimes, but on the other hand, the Anti-Corruption Law explicitly states that the return of state losses does not absolve the criminal liability of corruption perpetrators. Purposes of the Research: This research aims to analyze the aspect of legal certainty related to the application of peace fines in connection with corruption crimes, linked to national economic recovery efforts, and a comparative legal analysis in other countries regarding peace fines in the enforcement of corruption crimes. Methods of the Research: This research is a normative legal study with a conceptual, legislative, and comparative legal approach. Results Main Findings of the Research: The research results show that the application of restorative fines related to corruption crimes in connection with national economic recovery efforts does not yet guarantee legal certainty due to a conflict of rules between Article 35 paragraph 1 letter (k) of the Amendment to the Prosecutor's Law and Article 4 of the Anti-Corruption Law. The issue can be resolved with the principle of lex specialis derogat legi generali. The application of peace fines in England, the United States, and Saudi Arabia above shows that peace fines are of a global nature and constitute a general legal policy in their efforts to save a country's national economy from losses due to corruption. The implementation of peace fines in Indonesia to achieve legal certainty needs to consider several factors, such as clear regulatory revisions to avoid legal uncertainty and conflicts of rules in various laws and regulations.